1995
DOI: 10.1227/00006123-199508000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Spinal Cord Stimulation Reduces Ischemia in an Animal Model of Vasospasm

Abstract: Spinal cord stimulation (SCS) has been increasingly used in the treatment of ischemia caused by obliterative diseases in the extremities and in the cardiac circulation. The most promising effects have been obtained when physicians suspect that a major vasospastic component underlies the ischemic symptoms (e.g., as in Raynaud's disease). Despite the clinical success of this treatment method, little is known about the mechanisms underlying the pain relief it produces and its anti-ischemic effects. Most earlier e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…SCS is generally delivered both clinically and in experimental studies below motor threshold [33,38,66,76] and the majority of these use intesnities around 2/3 of motor threshold to produce analgesia [32,89]. The current study showed that intensities at 75% of motor threshold were less effective than 90% and 50% had no effect.…”
Section: Discussionmentioning
confidence: 65%
“…SCS is generally delivered both clinically and in experimental studies below motor threshold [33,38,66,76] and the majority of these use intesnities around 2/3 of motor threshold to produce analgesia [32,89]. The current study showed that intensities at 75% of motor threshold were less effective than 90% and 50% had no effect.…”
Section: Discussionmentioning
confidence: 65%
“…SCS was also used for the treatment against cardiac ischemia [40], or postoperative ileus [41]. The mechanism of vasodilation by SCS appears to be related to suppression of sympathetic activity [42], [43], as well as indirect activation of the brainstem or cerebellar vasomotor centers [6], [7], [44], and/or causing the release of rapid vasoactive substances such as nitric oxide or calcitonin gene-related peptide [45]–[47]. Moreover, SCS was accompanied by dilation of small arteries in the subarachnoid space without visible changes of intraparenchymal vessels in diameter [4], altogether supporting the concept of a humoral effect by SCS.…”
Section: Discussionmentioning
confidence: 99%
“…So far this difference cannot be explained [3,4,6,8,11,12,24,25]. Cerebral blood supply in rabbits is provided solely by the two internal carotid arteries and the vertebral arteries [26,27]. Cerebral blood vessels are densely innervated by sympathetic nerves that originate primarily from the superior cervical ganglia [28].…”
Section: Discussionmentioning
confidence: 99%